Promote or inhibit? The effect of the whole chain development of intellectual property on manufacturing firm performance - Yu, Liyan; Zhao, Chengfan (Frontiers in Psychology, 2023)
With the promotion of intellectual property strategy, the whole chain development of intellectual property environment faced by manufacturing firms has been improved, but the effect of the whole chain development of intellectual property on firm performance still needs to be studied. The purpose of this study is to investigate the impact of the whole chain development of intellectual property on different types of manufacturing firm performance. A panel regression model is constructed based on listed manufacturing firms from 2010 to 2020, and this is tested empirically. The results of the study show that the whole chain development of intellectual property has a promotion effect on manufacturing firm performance, among which the promotion effect of intellectual property services is the strongest, followed by intellectual property utilization and intellectual property creation, and the promotion effect of intellectual property management has a significant lag, while the relationship between intellectual property protection and manufacturing firms performance is significantly negative. The promotion effect of the whole chain development of intellectual property on different types of manufacturing firm performance is heterogeneous, and the promotion effect of the whole chain development of intellectual property on the performance of small-scale, non-state-owned, medium-high-technology manufacturing firms is stronger than that of large-scale, state-owned, low-technology manufacturing firms. This study not only extends the research direction of intellectual property, but also adds to the literature on firm performance. In addition, the findings of this paper help government authorities to further optimize the strategic layout of the whole chain development of intellectual property, promote manufacturing firms to solve internal management problems, and achieve a positive interaction between the top-level design of the intellectual property and the bottom-level logic of manufacturing firms.